Four new species of Lophilema Aurivillius, 1910 from East Africa (Lepidoptera, Erebidae, Arctiinae, Lithosiini) - Volynkin, Anton V. (Zootaxa, 2019)
Four new species of the genus Lophilema, Lophilema mbulu Volynkin, sp. nov. (Tanzania, Mbulu Mts.), Lophilema bilobata Volynkin, sp. nov. (Kenya, Aberdare Range), Lophilema nguru Volynkin, sp. nov. (Tanzania, Nguru Mts.), and Lophilema curva Volynkin, sp. nov. (Tanzania, Nguru Mts.) are described. Adults, male and female genitalia of new and related species are illustrated.